Kedudukan dan Pengelolaan Konflik dalam Organisasi Pendidikan - Bisri Mustofa; Sunhaji Sunhaji (Jurnal Kependidikan, 2020)
The purpose of this paper is to describe the position and management of conflict in educational organizations. it is a way of maintaining harmonious relationships at school. Harmonious relationships at school will make the learning environment comfortable and conducive to the learning process. Harmonious relationships at school will make the learning environment comfortable and conducive to the learning process. And vice versa, if the relationship between members of educational organizations is disharmonious, it can lead to an uncomfortable learning environment. This disharmonious relationship is usually caused by conflicts between individuals in schools. Conflict can become a serious problem in any organization, regardless of the form and level of complexity of the school organization, if the conflict is allowed to drag on without resolution. Therefore, the expertise to manage conflict is needed for every leader of educational organizations Keyword: Position and conflict management, Educational Organization